MPLICAȚIILE GREEN HUB–URILOR DIN UNIVERSITĂȚI ÎN DEZVOLTAREA COMPETENȚELOR VERZI - Cojocaru, Maria; Ulian, Galina; Năstase, Carmen-Eugenia (CEP USM, 2022)
Purpose of the article: the research of the GREEN/SUSTAINABLE HUB phenomenon in European universities under the aspects of: organization; activities; beneficiaries; opportunities for green skills training. Methodology: Based on the synthesis of specialized literature, it was hypothesized that Green Hubs have an important role in achieving SDG 2030. To achieve the goal, 7 European universities and the Green Office Model were analyzed. The accumulated data were processed with traditional research methods: analysis, synthesis, grouping, and comparison. Conclusions: The research carried out allowed the authors to conclude that Green Hubs in universities can contribute to the development of green skills through: education for sustainability (organization of master's programs; conceptualization and teaching of "green" courses, etc.); carrying out research projects on sustainability topics; carrying out interaction activities and promotion of good sustainable practices. To facilitate the establishment of a Green Hub, student communities, guided by academic staff or researchers, could adopt the Green Office Model by joining the Green Office Movement. Implications: the obtained results will allow student communities, and university decision -makers to conceptualize and establish Green Hubs for the training of students' green skills.
Keywords: Green-Hub; green skills